2022
DOI: 10.1111/hex.13498
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the psychosocial and mental health of HIV‐positive women in China from 2015 to 2020: Results from two cross‐sectional surveys

Abstract: Background: The human immunodeficiency virus (HIV) continues to be one of the major public health challenges in the world. Despite the advancement in medication and changes in views towards HIV in Chinese society, little is known about the changes in the psychosocial and mental health of HIV-positive women in recent years.Objectives: The present study examined the change in depression, anxiety, stigma, relationship with the child, intimacy with a partner, and social support from family, friends, and health pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It may be that couples who have a fulfilling sex life anticipate less stigma from outside their relationships. Some PLHIV have reported that HIV limits or reduces sexual intimacy [ 84 86 ]. Thus, couples who report high sexual satisfaction despite living with HIV may have particularly healthy and resilient relationships, which also provide a buffer against stigma.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that couples who have a fulfilling sex life anticipate less stigma from outside their relationships. Some PLHIV have reported that HIV limits or reduces sexual intimacy [ 84 86 ]. Thus, couples who report high sexual satisfaction despite living with HIV may have particularly healthy and resilient relationships, which also provide a buffer against stigma.…”
Section: Discussionmentioning
confidence: 99%